Continuous ethanol fermentation of lactose by a recombinant flocculating saccharomyces cerevisiae strain - Domingues, Lucília (1999)
Alcohol fermentation of lactose was investigated using a recombinant flocculating Saccharomyces cerevisiae, expressing the LAC4 (coding for b-galactosidase) and LAC12 (coding for lactose permease) genes of Kluyveromyces marxianus. Data on yeast fermentation and growth on a medium containing lactose as the sole carbon source are presented. In the range of studied lactose concentrations, total lactose consumption was observed with a conversion yield of ethanol close to the expected theoretical value. For the continuously operating bioreactor, an ethanol productivity of 11 g L−1 h−1 (corresponding to a feed lactose concentration of 50 g L−1 and a dilution rate of 0.55 h−1) was obtained, which is 7 times larger than the continuous conventional systems. The system stability was confirmed by keeping it in operation for 6 months.